2011
DOI: 10.1038/nphys2170
|View full text |Cite
|
Sign up to set email alerts
|

High-fidelity quantum driving

Abstract: Accurately controlling a quantum system is a fundamental requirement in quantum information processing and the coherent manipulation of molecular systems. The ultimate goal in quantum control is to prepare a desired state with the highest fidelity allowed by the available resources and the experimental constraints. Here we experimentally implement two optimal high-fidelity control protocols using a two-level quantum system comprising Bose-Einstein condensates in optical lattices. The first is a short-cut proto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
521
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 459 publications
(526 citation statements)
references
References 27 publications
5
521
0
Order By: Relevance
“…(iii) θ has to be determined from Eq. (13). (iv) The fast-forward potential can be calculated from Eq.…”
Section: Connection With the Fast-forward Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…(iii) θ has to be determined from Eq. (13). (iv) The fast-forward potential can be calculated from Eq.…”
Section: Connection With the Fast-forward Approachmentioning
confidence: 99%
“…Among other approaches let us mention (i) a transitionless tracking algorithm or "counterdiabatic" approach that adds to the original Hamiltonian extra terms to cancel transitions in the adiabatic or superadiabatic bases [8][9][10][11][12][13]; (ii) inverse engineering of the external driving [3,4,6,[21][22][23][24][25][26] based on Lewis-Riesenfeldt invariants [27], which has been applied in several expansion experiments [25,26]; (iii) optimal control (OC) methods [5,7,14,16], sometimes combined with other methods to enhance their performance [4,5,7]; (iv) the fast-forward (FF) approach advocated by Masuda and Nakamura [19,28]; (v) parallel adiabatic passage [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In particular the Chopped Random Basis (CRAB) technique offers an efficient way to implement optimal control, based on an expansion of the control field onto a truncated basis [14,15]. Recently it has been shown that optimal control allows for reaching the Quantum Speed Limit (QSL), the minimal time required by physical constraints to perform a given transformation, in spin chains [19,20], cold atoms in optical lattices [21], Bose-Einstein condensates in atom chip experiments and in crossing of quantum phase transitions [23]. Indeed, CRAB control makes it possible to reduce the time of the transformation down to the QSL, which scales as 1/∆, obtaining a quadratic speedup of the protocol with re- spect to the adiabatic one.…”
mentioning
confidence: 99%
“…The second scheme we consider is the CP protocol [25]. This scheme has been proved to be capable to control a system described by a LZ-type Hamiltonian at the maximum speed allowed by quantum mechanics [24,26].…”
Section: B Efficiency and Speed Of Control Protocols For Csd Navigationmentioning
confidence: 99%
“…These various control strategies include the use of analytically wellestablished phenomena like the paradigmatic LandauZener (LZ) transition [12][13][14], Landau-Zener-Stückelberg interferometry [15,16], the composite pulse (CP) protocol and several other two-level control strategies [12,[24][25][26][27], and OCT [18][19][20][21][22][23]. For the experimental control strategies, as can be seen in [10,[15][16][17], the first stage is the measurement of the charge stability diagram (CSD).…”
Section: Introductionmentioning
confidence: 99%